Football and colonialism: body and popular culture in urban Mozambique: By Nuno Domingos. Athens, OH: University of Ohio Press, 2017 - Cleveland, Todd (Acta Academica: Critical views on society, culture and politics, 2018)
Nuno Domingos’s Football and Colonialism examines the introduction and diffusion of soccer in the former Portuguese colony of Mozambique. More than just a sports history, the book employs soccer as a prism through which to trace the shifting interactions between Africans and Europeans in Mozambique and, in particular, the colonial capital Lourenc?o Marques (now Maputo).